Shall we call them "telomere-mediated"? Renaming the idiopathic after the cause is found. Issue 6 (December 2016) - Merck, Samantha J.; Armanios, Mary
Short of lung scarring, the idiopathic interstitial pneumonias (IIPs) primarily share their poorly understood aetiology. Attempts to identify features that refine the distinctions between IIP diagnostic categories, based on pathologic and radiographic criteria, have led to recent revisions in their evaluation [1, 2]. The consensus recommendation relies on multidisciplinary assessment to clarify an IIP diagnosis [2]. However, there still remains a relatively low concordance rate across groups of experienced clinicians [3, 4] and the heterogeneity of the clinical course within IIP subtypes poses a challenge to using these categories when making decisions at the bedside [2]. This editorial contextualises the findings of two articles in this ERJ issue, and proposes new terminology http://ow.ly/SRcc305Mvbn